Perioperative management of children with urea cycle disorders. Issue 7 (25th May 2020) - Del Río, Cristina; Martín‐Hernández, Elena; Ruiz, Alicia; Quijada‐Fraile, Pilar; Rubio, Paloma
Abstract: Background: Urea cycle disorders are congenital metabolism errors that affect ammonia elimination. Clinical signs and prognosis are strongly influenced by peak ammonia levels. Numerous triggers associated with metabolic decompensation have been described with many of them, including fasting or stress, being related to the perioperative period. Aims: We aimed to assess perioperative complications in pediatric patients with urea cycle disorders requiring general anesthesia in our center. Methods: We reviewed the clinical history of all the pediatric patients with a confirmed urea cycle disorders diagnosis requiring surgery or a diagnostic procedure with anesthesia between January 2002 and June 2018. Results: We included 33 operations (major surgery, minor surgery, and diagnostic procedures) carried out on 10 patients via different anesthetic techniques. We observed the following complications: intraoperative hyperglycemia in one case, postoperative vomiting in eight cases, and slightly increased postoperative ammonia levels (54, 59, and 69 µmol/L) with normal preoperative levels in three cases without associated metabolic decompensation. There were two cases of perioperative hyperammonemia (72 and 69 µmol/L) secondary to preoperative metabolic decompensation (137 and 92 µmol/L) with the levels progressively dropping and normalizing in the first 24‐48 hours, respectively. Conclusions: Procedures under anesthesia on pediatric patients with urea cycle diseases should be performed by experienced multidisciplinary teams at specialized centers. Perioperative management focused on avoiding catabolism (especially during fasting) and monitoring signs associated with metabolic decompensation to allow for its early treatment should be included in routine anesthetic techniques for children with urea cycle disorders.